Three‐dimensional regions‐of‐interest–based intra‐operative four‐dimensional soft tissue perfusion imaging using a standard x‐ray system with no gantry rotation: A simulation study for a proof of concept. Issue 12 (22nd October 2020) - Taguchi, Katsuyuki; Sauer, Thomas J.; Segars, W. Paul; Frey, Eric C.; Xu, Jingyan; Liapi, Eleni; Stayman, J. Webster; Hong, Kelvin; Hui, Ferdinand K.; Unberath, Mathias; Du, Yong
Abstract : Purpose: Many interventional procedures aim at changing soft tissue perfusion or blood flow. One problem at present is that soft tissue perfusion and its changes cannot be assessed in an interventional suite because cone‐beam computed tomography is too slow (it takes 4–10 s per volume scan). In order to address the problem, we propose a novel method called IPEN for I ntra‐operative four‐dimensional soft tissue PE rfusion using a standard x‐ray system with N o gantry rotation. Methods: IPEN uses two input datasets: (a) the contours and locations of three‐dimensional regions‐of‐interest (ROIs) such as arteries and sub‐sections of cancerous lesions, and (b) a series of x‐ray projection data obtained from an intra‐arterial contrast injection to contrast enhancement to wash‐out. IPEN then estimates a time‐enhancement curve (TEC) for each ROI directly from projections without reconstructing cross‐sectional images by maximizing the agreement between synthesized and measured projections with a temporal roughness penalty. When path lengths through ROIs are known for each x‐ray beam, the ROI‐specific enhancement can be accurately estimated from projections. Computer simulations are performed to assess the performance of the IPEN algorithm. Intra‐arterial contrast‐enhanced liver scans over 25 s were simulated using XCAT phantom version 2.0 with heterogeneous tissue textures and cancerous lesions. The following four sub‐studies were performed: (a) The accuracy of the estimated TECs with overlapped lesions was evaluated at various noise (dose) levels with either homogeneous or heterogeneous lesion enhancement patterns; (b) the accuracy of IPEN with inaccurate ROI contours was assessed; (c) we investigated how overlapping ROIs and noise in projections affected the accuracy of the IPEN algorithm; and (d) the accuracy of the perfusion indices was assessed. Results: The TECs estimated by IPEN were sufficiently accurate at a reference dose level with the root‐mean‐square deviation (RMSD) of 0.0027 ± 0.0001 cm −1 or 13 ± 1 Hounsfield unit (mean ± standard deviation) for the homogeneous lesion enhancement and 0.0032 ± 0.0005 cm −1 for the heterogeneous enhancement ( N  = 20 each). The accuracy was degraded with decreasing doses: The RMSD with homogeneous enhancement was 0.0220 ± 0.0003 cm −1 for 20% of the reference dose level. Performing 3 × 3 pixel averaging on projection data improved the RMSDs to 0.0051 ± 0.0002 cm −1 for 20% dose. When the ROI contours were inaccurate, smaller ROI contours resulted in positive biases in TECs, whereas larger ROI contours produced negative biases. The bias remained small, within ± 0.0070 cm −1, when the Sorenson–Dice coefficients (SDCs) were larger than 0.81. The RMSD of the TEC estimation was strongly associated with the condition of the problem, which can be empirically quantified using the condition number of a matrix A z that maps a vector of ROI enhancement values z to projection data and a weighted variance of projection data: a linear correlation coefficient ( R ) was 0.794 ( P  < 0.001). The perfusion index values computed from the estimated TECs agreed well with the true values ( R  ≥ 0.985, P  < 0.0001). Conclusion: The IPEN algorithm can estimate ROI‐specific TECs with high accuracy especially when 3 × 3 pixel averaging is applied, even when lesion enhancement is heterogeneous, or ROI contours are inaccurate but the SDC is at least 0.81.